2013
DOI: 10.3329/bjch.v36i3.14275
|View full text |Cite
|
Sign up to set email alerts
|

Role of CSF C-Reactive Protein for the Differentiation of Bacterial Meningitis from Aseptic Meningitis in Children

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…18 Khanam R et al in their study reported Sensitivity, Specificity, Positive Predictive Value (PPV) and Negative Predictive Value (NPV) to be 35%, 100%, 100% and 53.6% respectively. 17 CRP migration to CSF is not properly explained in literature. CSF-CRP levels were fund to be lower than that of serum CRP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Khanam R et al in their study reported Sensitivity, Specificity, Positive Predictive Value (PPV) and Negative Predictive Value (NPV) to be 35%, 100%, 100% and 53.6% respectively. 17 CRP migration to CSF is not properly explained in literature. CSF-CRP levels were fund to be lower than that of serum CRP.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, Khanam R had reported only 35% of bacterial meningitis cases to be CSF-CRP positive. 17 Our study reported the CSF-CRP to have a Sensitivity, Specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV) and Diagnostic Accuracy (DA) of 72.92%, 85.71%, 85.71%, 73.47% and 78.89% respectively. Singh N et al in their study concluded that CSF-CRP had a sensitivity of 84%, specificity of 100% and a positive predictive value of 100%.…”
Section: Discussionmentioning
confidence: 99%